New Dutch Swing: An In-Depth Examination of Amsterdam's Vital and Distinctive Jazz Scene - Whitehead, Kevin (New York Billboard Books, 1999)
A thriving creative music scene based on jazz, classical music and absurdism, is described in-depth from the perspective of an American music critic's eyewitness accounts. The book explores one of Europe's most vital "alternative musical universes", where improvisers and composers band together to create a distinctive sound. It combines oral history with critical evaluations of key recordings and contemporary club and concert appearances, and also discusses various sociological and linguistic factors that affect Dutch jazz and its connections to American music.
Keywords: 20th Century (1901-2000); Jazz; Music history; Amsterdam (Netherlands)